2023
DOI: 10.24171/j.phrp.2023.0033
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the prevalence of oral manifestations in COVID-19 patients: a systematic review

Ankita Gupta,
Kriti Shrivastav,
Amit Agrawal
et al.

Abstract: Objectives: Patients with coronavirus disease 2019 (COVID-19) present with a variety of oral manifestations. Therefore, we conducted a systematic review to estimate the prevalence of oral lesions among COVID-19 patients. Methods: An extensive literature search of several electronic bibliographic databases (PubMed, Scopus, Science Direct, Litcovid) was conducted to retrieve all articles published in the English language from January 1, 2020 to March 31, 2023 that reported the prevalence of oral manifestations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
(515 reference statements)
0
2
0
Order By: Relevance
“…Approximately 32% and 35% of COVID-19 related oral symptoms are associated with salivary gland involvement and xerostomia, respectively (Gupta et al, 2023). We also found that salivary glands, especially serous acini, were susceptible to SARS-CoV-2 (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Approximately 32% and 35% of COVID-19 related oral symptoms are associated with salivary gland involvement and xerostomia, respectively (Gupta et al, 2023). We also found that salivary glands, especially serous acini, were susceptible to SARS-CoV-2 (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 55%
“…COVID-19 mainly manifests as acute respiratory distress syndrome (Huang et al, 2020), but accumulating evidence has shown that oral symptoms have a relatively high incidence. A research involving 79 studies with data from 13,252 patients showed that taste disorders (48%), dry mouth (35%), and oral ulceration (21%) have been identified as the prevalent symptoms of COVID-19 (Tan et al, 2022;Gupta et al, 2023). Although COVID-19-related dysgeusia is usually transient, approximately 5% of patients develop taste disorders that persist for more than four weeks.…”
Section: Introductionmentioning
confidence: 99%